Effect of gamma irradiation on the critical heat flux of sintered nano-coated surfaces. (October 2022) - Rahimian, A.; Kazeminejad, H.; Khalafi, H.; Akhavan, A.; Mirvakili, M.
Abstract: The electrophoretic deposition (EPD) technique was used to manufacture uniform SiO2, Al2 O3, ZrO2, and TiO2 thin film coatings on thin steel plates (1.5 mm by 90 mm) to study heat transport properties when in contact with water at boiling temperature. To find the thickness and uniformity of the coatings, scanning electron microscope (SEM) images were made. The captured images showed that the coating thickness is uniformly increased by the EPD method. To investigate the effect of sintering, the coated plates were placed in a furnace at various temperatures. To investigate the effect of gamma irradiation on the critical heat flux (CHF) of the coated surfaces, the test specimens were irradiated in a gamma cell with different dose rates, and then BET, SEM, and EDS analyses were performed. Significant enhancement in CHF, for the hydrophilic surfaces, can be achieved by the EPD method. The results showed that the CHF for the sintered nano-coated surfaces, SiO2, Al2 O3, ZrO2, and TiO2, increase by 24%, 23%, 19%, and 10%, compared to those of unsintered nanocoated surfaces, respectively. It was observed that irradiation significantly decreases the maximum pore diameter while it increases the porosity, pore surface area, and pore volume. The CHF of the nano-coated surfaces irradiated at 300 kGy increased by 12%, 8%, 5%, and 12% for SiO2, Al2 O3, ZrO2, and TiO2, respectively. Nevertheless, the effect of gamma irradiation on the sintered surfaces was insignificant. Highlights: The EPD method is used to create a uniform SiO2, Al2 O3, ZrO2, and TiO2 nanoparticle deposition on the steel plates. The effect of gamma irradiation on the CHF of the sintered nano-coating surfaces is investigated. SEM and BET are used to analyze the surface morphology. Gamma irradiation significantly decreases the maximum pore diameter and increases the CHF.